Neurofunctional Evaluation of Young Male Offspring of Rat Dams with Diabetes Induced by Streptozotocin. (22nd September 2011) - Delascio Lopes, Carla; Sinigaglia-Coimbra, Rita; Mazzola, Jacqueline; Camano, Luiz; Mattar, Rosiane
Abstract : Diabetes mellitus (DM) is a complex disease, being one of the most prevalent diseases worldwide. As a consequence, pregnancy-associated diabetes is increasingly common. Given the numerous studies about the influence of diabetes on offspring of diabetic rat dams, the neurological outcome is of outmost importance. This paper aimed at evaluating the neurofunctional performance of young male offspring of rat dams with diabetes induced by streptozotocin. Diabetes was induced in Wistar female rats by streptozotocin administration, while control groups received vehicle injection. At two-month survival period, male offspring from each group were randomized to the water maze Morris test, in order to assess their neurofunctional status. There was no significant difference between the groups as assessed by the Morris water maze test for spatial reference task. Our results point to the need of further investigation on the offspring neurofunctional performance.